Nursing Care for Chronic Pain in Gout Arthritis Patients Using Red Ginger Compress: A Case Study: Case Study in the Working Area of Kebonsari Health Center, Pasuruan - Dinda Maulidyah Novifah; Erik Kusuma; Dwining Handayani; Syaifuddin Kurnianto; Hardiyah Novita Arifin (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: Gout arthritis is a form of joint inflammation caused by the accumulation of uric acid crystals in the body. This condition causes recurrent pain that can develop intochronic pain and impact activity limitations as well as a decrease in quality of life. The aimof this study is to analyze the application of red ginger compress in nursing care formanaging chronic pain in patients with gout arthritis. Objective: This study used a descriptive case study approach on one patient with chronicgout arthritis at Kebonsari Community Health Center. The patient received standardpharmacological therapy (allopurinol) combined with red ginger compress applied twicedaily for seven days. Pain intensity was measured using the Numeric Rating Scale (NRS).Results: After seven days of intervention, there was a decrease in the pain scale from 6 to2, a reduction in grimacing and restlessness, a decrease in protective posture, animprovement in sleep quality, a pulse rate of 82 beats per minute, blood pressure of 130/80mmHg, and a respiration rate of 21 breaths per minute. Conclusions: Red ginger compress therapy has proven effective in helping to reducechronic pain in patients with gout arthritis. This intervention can be used as acomplementary method in nursing practice, particularly to improve patient comfort andphysical function without side effects.